2017
DOI: 10.5194/npg-2017-8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights on the three-dimensional Lagrangian geometry of the Antarctic Polar Vortex

Abstract: Abstract. The present paper introduces an algorithm for the visualization, analysis and verification of transport and mixing processes in three-dimensional atmospheric flows. This algorithm is based on the methodology of Lagrangian descriptors (LDs), a technique from Dynamical Systems Theory. The algorithm is applied to reanalysis data in order to illustrate the evolution of the flow above Antarctica during a period of rapid changes in the southern spring of 1979. The evolution of Lagrangian coherent structure… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…This saddle is placed close to an Arctic area, the Barrow Canyon, for which upwelling motions have been reported (Lin et al ); thus the 2D approach taken for our description requires further verification. According to fully 3D Lagrangian studies in geophysical flows such as those reported in ((Curbelo et al ); ()), a class of 3D flows commonly occurring in this context possesses Lagrangian structures consisting of a stack of 2D Lagrangian structures (see Garcia‐Garrido et al , ). These types of structures are produced when vertical motions are small in comparison to horizontal velocity components, which are the dominant ones.…”
Section: Lagrangian Analysis Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This saddle is placed close to an Arctic area, the Barrow Canyon, for which upwelling motions have been reported (Lin et al ); thus the 2D approach taken for our description requires further verification. According to fully 3D Lagrangian studies in geophysical flows such as those reported in ((Curbelo et al ); ()), a class of 3D flows commonly occurring in this context possesses Lagrangian structures consisting of a stack of 2D Lagrangian structures (see Garcia‐Garrido et al , ). These types of structures are produced when vertical motions are small in comparison to horizontal velocity components, which are the dominant ones.…”
Section: Lagrangian Analysis Resultsmentioning
confidence: 99%
“…Horizontal velocities may vary with the vertical coordinate, and this could cause differences in the Lagrangian patterns at different levels; however, the continuity of the horizontal velocities with respect to the vertical coordinate is responsible for the preservation of major Lagrangian features at different slices (see the discussion in sect. 2 of (Curbelo et al ) for further details on the type of problem described). A typical feature of these flows is, for instance, the vertical extension of the hyperbolic trajectories throughout the vertical coordinate, forming a mathematical object known as a normally hyperbolic invariant manifold (NHIM; (Mezic and Wiggins, ; Wiggins, )).…”
Section: Lagrangian Analysis Resultsmentioning
confidence: 99%
See 3 more Smart Citations